1970
DOI: 10.1126/science.169.3949.952
|View full text |Cite
|
Sign up to set email alerts
|

New Wheats and Social Progress

Abstract: Will the upward trend in all food production, so dramatically exemplified by the new wheats, be adequate to meet the needs of the growing population? Yes, for a while. No one knows for how long (14). The prophets of doom will undeniably be proved right in the long run unless their basic assumptions are nullified by concrete acts, and soon. At some point in time, either a zero population growth must be achieved or vast new sources of food must be developed, and purchasing power increased. There is nothing on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1972
1972
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The classical example of selecting for a plant's ability to utilize N efficiently was Norman Borlaug's introduction of dwarfing genes and selection for the resulting semidwarf high yielders. These genes (Rht-B1 and Rht-D1), which were originally derived from a cross between a Japanese variety of dwarf wheat (Norin 10) and a high-yielding American variety (Brevor), became the model for the use of dwarfing genes to allow plants to use higher levels of N without the lodging common in the tall varieties (104). The dwarfing genes altered stem strength and plant architecture and indirectly generated plants that could produce much higher yield under high (standardized) levels of fertilizer and hence had enhanced NUE (104).…”
Section: Defining Nitrogen Use Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…The classical example of selecting for a plant's ability to utilize N efficiently was Norman Borlaug's introduction of dwarfing genes and selection for the resulting semidwarf high yielders. These genes (Rht-B1 and Rht-D1), which were originally derived from a cross between a Japanese variety of dwarf wheat (Norin 10) and a high-yielding American variety (Brevor), became the model for the use of dwarfing genes to allow plants to use higher levels of N without the lodging common in the tall varieties (104). The dwarfing genes altered stem strength and plant architecture and indirectly generated plants that could produce much higher yield under high (standardized) levels of fertilizer and hence had enhanced NUE (104).…”
Section: Defining Nitrogen Use Efficiencymentioning
confidence: 99%
“…These genes (Rht-B1 and Rht-D1), which were originally derived from a cross between a Japanese variety of dwarf wheat (Norin 10) and a high-yielding American variety (Brevor), became the model for the use of dwarfing genes to allow plants to use higher levels of N without the lodging common in the tall varieties (104). The dwarfing genes altered stem strength and plant architecture and indirectly generated plants that could produce much higher yield under high (standardized) levels of fertilizer and hence had enhanced NUE (104). However, since the selection of these highyielding, semidwarf wheat varieties on high N, what has been observed on a global scale, especially in developed countries, is a plateauing of any more yield increases, even while the crops are grown using the same high N levels.…”
Section: Defining Nitrogen Use Efficiencymentioning
confidence: 99%
“…Previous studies have shown that after long‐term natural selection and artificial directional breeding, wheat cultivars tend to show shorter, stiffer stems, higher harvest index, fewer tillers, and greater adaptability, especially under relatively (but not severe) nutrient‐deficient conditions (Brancourt‐Hulmel et al, 2003, Shearman et al, 2005). Dwarfing genes alter stem strength and plant architecture, indirectly generating plants that produce much greater yield and NUE but decreased biomass (Reitz 1970). Shearman et al (2005) found that a linear increase in grain yield was positively correlated with both harvest index and aboveground biomass.…”
Section: Discussionmentioning
confidence: 99%